Identity in formation the Russian-speaking populations in the near abroad - Laitin, David D. 1945- (Cornell Univ. Press, 1998)
Since the collapse of the Soviet Union, nationality groups have claimed sovereignty in the new republics bearing their names. With the ascendance of these titular nationality groups, Russian-speakers living in the post-Soviet republics face a radical crisis of identity. That crisis is at the heart of David D. Laitin's book. Laitin portrays these Russian-speakers as a "beached diaspora" since the populations did not cross international borders; the borders themselves receded. He asks what will become of these populations. Will they learn the languages of the republics in which they live and prepare their children for assimilation? Will they return to a homeland many have never seen? Or will they become loyal citizens of the new republics while maintaining a Russian identity? On the basis of ethnographic field research, discourse analysis, and mass surveys, Laitin analyzes trends in Estonia, Latvia, Kazakhstan, and Ukraine.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Etnisch bewustzijn; Russen; Nationalismus; Politik; Russian language -- Political aspects -- Former Soviet republics; Nationalism -- Former Soviet republics; Russisch; Nationalitätenfrage; Nachfolgestaaten; Former Soviet republics -- Ethnic relations; Sowjetunion